Historical Research Survey Database - Jock C Currie; Colin G Attwood; Wayne S Goschen; Lara J Atkinson (South African Environmental Observation Network, 2013)
The historical survey data were transcribed from the Department of Agriculture `Report of the Marine Biologist` (pre-1900) and `Report of the Government Biologist` (1900-1904) publications for the period of 1897-1904. The data from 1920-1949 were transcribed from the Union of South Africa series of `Fisheries and Marine Biological Survey` reports, which in 1935 became the Department of Commerce and Industries` `Fisheries and Marine Biological Survey Division` reports, and from 1937 onwards were published as `The Division of Fisheries Annual Reports`. Although they changed names, these reports essentially represent an (incomplete) series that documents fisheries and oceanography-related surveys and investigations in South Africa (and Namibia and Mozambique) during those periods. The majority of the digitized records stem from trawls, but samples from dredges, plankton nets and other gear are also included. Whereas the initial reports appear to document all biological specimens collected during these surveys, the reports of 1899-1904 focus on trawl catches only, listing roughly 20 common fish species and frequently grouping chondrichthyans into categories such as `sharks`, `sting rays`, `skates` and `dogfish`, with a broad `other fish` group encompassing all taxa not listed separately. During the period 1920-1932, all specimens (collected by various gear) seem to have been recorded, although the identification of some taxa (especially invertebrates) was frequently to a relatively coarse level.
Keywords: historical trawl survey; fisheries; baseline data; Gilchrist; von Bonde